Improving Learning Outcomes of Citizenship Subject Topic State Institutions Through Concept Attaintment Learning Model Application of Grade VI Students at SDN Tegal Besar 03 Kecamatan Kaliwates Kabupaten Jember First Semester Academic Year 2013/2014 - Sri Dwi Ningsih (History Education, University of Jember, 2018)
The deficiency of education quality has become a main issue in improving the nation. A measure which can be attempted to deal with the issue is dealing with several factors which block learning program achievements. Concept attainment model is a teaching strategy focuses upon concept attachment towards students by engaging samples from lesson presented. Those samples will likely be presented prior to learning orientation, then teacher commands students to observe and grasp the content. Observation process towards samples will construct students’ abstraction, thus they obtain the picture which relates to the next lesson. This classroom action research was conducted at least 2 cycle, in which each cycle involves 4 stages namely planning, implementation, observation, and relection. The reseacher concludes that concept attainment learning model application is able to improve students’ learning outcome dan simplifies students to present and understand concept truthfulness of citizenship (PKn) subject topic State Institution. This learning model is considered to be helpful in improving students of all ages upon understanding map concept and hypothesis examination practice.Keywords : Learning Outcomes, Concept Attainment Learning Model